COMMUNITY PARTICIPATION IN LOCAL BUDGET MAKING TOWARDS A PARTICIPATORY BUDGETING MODEL - Mardihang; Novarlia, Irena; Merung, Arteurt Yoseph; Sukomardojo, Tekat; Hasibuan, Masnilam (Alqaprint Jatinangor, 2023)
This study explores the role of community participation in local budget making, aiming to develop a model for participatory budgeting that enhances transparency, accountability, and public engagement in fiscal decision-making. Through a mixed-methods approach, the research analyzes the extent and impact of community involvement in local budget processes across various municipalities. The study draws on quantitative data from budgetary records and qualitative insights from interviews with local officials and community members. Findings indicate that increased community participation leads to more equitable and effective budget allocations, aligning public spending with community needs and priorities. The study also identifies barriers to participation, including limited public awareness and institutional resistance. Based on these findings, the study proposes a participatory budgeting model that incorporates structured community input mechanisms, capacity-building initiatives, and policy recommendations to foster greater civic engagement in local budgeting. This model aims to bridge the gap between local governments and their constituents, promoting a more democratic and responsive budgeting process.